2017
DOI: 10.1002/cbic.201700330
|View full text |Cite
|
Sign up to set email alerts
|

Switching Futile para‐Quinone to Efficient Reactive Oxygen Species Generator: Ubiquitin‐Specific Protease‐2 Inhibition, Electrocatalysis, and Quantification

Abstract: Understanding the correlation between structural features of small-molecule drugs and their mode of action is a fascinating topic and crucial for the drug-discovery process. However, in many cases, knowledge of the exact parameters that dictate the mode of action is still lacking. Following a large screening for ubiquitin specific protease 2 (USP2) inhibition, an effective para-quinone-based inhibitor with an unclear mode of action was identified. To gain a deeper understanding of the mechanism of inhibition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Within this type of enzymes, ubiquitin-specific proteases 1 and 2 (USP1 and USP2) are linked with DNA damage repair. Particularly, USP2 has been associated with apoptosis resistance by cancer cells through stabilization of Fas and cyclin D1 [59]. It has been reported that both enzymes are susceptible to ROS and are inhibited by the natural ortho -quinone β-lapachone ( 12 ), suggesting that they are interesting targets for the development of compounds for cancer therapy.…”
Section: Main Textmentioning
confidence: 99%
“…Within this type of enzymes, ubiquitin-specific proteases 1 and 2 (USP1 and USP2) are linked with DNA damage repair. Particularly, USP2 has been associated with apoptosis resistance by cancer cells through stabilization of Fas and cyclin D1 [59]. It has been reported that both enzymes are susceptible to ROS and are inhibited by the natural ortho -quinone β-lapachone ( 12 ), suggesting that they are interesting targets for the development of compounds for cancer therapy.…”
Section: Main Textmentioning
confidence: 99%
“…[22] Thed esign of these probes allows the enzymatic hydrolysis and chemiexcitation process to occur concurrently under physiological conditions with remarkable light-emission intensities. [23][24][25][26][27] We sought to use this design strategy to prepare achemiluminescence probe that is suitable for activation by cathepsin B. Herein, we report the development of the first chemiluminescence probe for the detection and imaging of cathepsin B that is suitable for use under physiological conditions.…”
mentioning
confidence: 99%
“…Removal of the substrate by an enzyme or an analyte of choice triggers the direct chemiexcitation mechanism of the dioxetane luminophore. This meant that, for the first‐time, an intense light‐emission signal could be obtained under physiological conditions to image endogenous molecular activities in vitro and in vivo . The insights obtained from analysis of the chemiexcitation pathway prompted us to develop a distinct molecular unit that intrinsically integrates a chemiexcitation turn‐on signal with a self immolative release mechanism .…”
Section: Figurementioning
confidence: 99%